An advanced pressure pulsation model for external gear pump. (15th March 2023) - Xu, Wengang; Wang, Zhiying; Zhou, Zheng; Sun, Chuang; Zhang, Junhui; Yan, Ruqiang; Chen, Xuefeng
Highlights: Considering the lateral clearance and manufacturing error, a new dynamic model of external gear pump pressure pulsation is proposed. A lateral clearance model is proposed to evaluate the nonlinear variation of end face clearance under different working conditions. A manufacturing error model is proposed, and the influence of manufacturing error on pressure pulsation is analyzed. An indirect measurement method is proposed to optimize the pressure pulsation model of external gear pump. Abstract: Pressure pulsation is the inherent characteristic of external gear pump. This paper presents a new pressure pulsation model by considering the lateral clearance and manufacturing error. Firstly, inspired by the Archard model, the maximum roughness peak of lateral bushing surface with or without wear are measured by laser confocal microscope, which is to obtain the change law of lateral clearance indirectly and construct the lateral clearance model. Then, the manufacturing error model is constructed based on the long and short period errors of the master-slave gear acquired by the gear measuring center. Meanwhile, according to the boundary constraints, the lateral clearance model and the manufacturing error model are embedded into the lumped parametric model of the pressure pulsation to realize updating. Finally, the robustness of the new pressure pulsation model under different working conditions is verified, and the nature of the influence of the lateral clearance model and manufacturing error model on pressure pulsation is revealed. Experimental results on an external gear pump validate the merits of the new model in both time domain and frequency domain. The results can provide helpful guidance to understand the mechanism of external gear pump pressure pulsation.